A case of IgG4-related cholangitis responding to a steroid agent - Suenaga, Masahiro; Horiguchi, Yuji; Kurumiya, Takashi (Tando, 2007)
A 74-year-old male reffered to our clinic due to jaundice, body weight loss, and an upper abdominal mass. Laboratory data indicated obstructive liver damage and autoimmune disorder. Sonography disclosed dilatation of intra- and extra-hepatic bile ducts accompanied by a pancreatic head mass, measuring 4.3cm in diameter. The mass was well enhanced on contrast-enhanced dynamic CT images, and inflammatory tumor was suspected due to elevation of blood IgG4 level. Additionally uneven thickness of upper bile ducts and gallbladder wall was observed, suggesting sclerotic cholangitis. Steroid hormone therapy in a primary dose of 30mg/day resulted in dramatic improvement of symptoms and blood chemistry data in addition to shrinkage of pancreatic mass and decreased thickness of bile ducts.